The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/pedi.12227
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in month of diagnosis in children with type 1 diabetes registered in 23 European centers during 1989-2008: little short-term influence of sunshine hours or average temperature

Abstract: word count: 250 excluding headingsMain text word count: 2,564 including Table and Figure legends Tables and Figures: Tables (2) Methods Twenty-three population-based registers recorded date of diagnosis for new cases of type 1 diabetes among children under 15 years. Tests for seasonal variation in monthly counts aggregated over the 20 year period were conducted. Time series regression was used to investigate if sunshine hour and average temperature data were predictive of the 240 monthly diagnosis counts aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 38 publications
8
42
0
Order By: Relevance
“…This finding is in accordance with most previous studies on the seasonality of the diagnosis of T1DM [7,12,14,15,18,20]. Although an initial study from 2001 found no relationship between the incidence of T1DM diagnosis and the season among several countries in Europe, a recent study within Europe based on accumulated data from 23 European registries over a 20-year observation period reported seasonal variation in T1DM diagnosis with highest IR in November to February among all patients and in both sexes in most countries [20].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding is in accordance with most previous studies on the seasonality of the diagnosis of T1DM [7,12,14,15,18,20]. Although an initial study from 2001 found no relationship between the incidence of T1DM diagnosis and the season among several countries in Europe, a recent study within Europe based on accumulated data from 23 European registries over a 20-year observation period reported seasonal variation in T1DM diagnosis with highest IR in November to February among all patients and in both sexes in most countries [20].…”
Section: Discussionsupporting
confidence: 87%
“…Recently, the Eurodiab study described seasonality with peak incidence in the winter in 21 of the 23 European countries included [20]. As the Netherlands has not been participating in this register since 1999, seasonality patterns in diagnosis of T1DM in the Netherlands are unknown.…”
Section: Introduction Key Notesmentioning
confidence: 96%
“…The greatest number of cases were diagnosed during autumn and winter months. Seasonality in monthly case counts of T1DM is apparent in most EURODIAB centers, in all age groups and both sexes 6 . In conclusion, the results of this study indicated that T1DM incidence was still increasing in younger age groups, especially in boys aged 0-4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Many registries describe seasonal variation in the date of T1DM diagnosis, with a note that the disease is most often diagnosed during winter months 6 . This is associated with the number of sunny days, which is important for the synthesis of vitamin D 7 and for seasonal infections 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, an additional explanatory factor for our results might be the fact that our country's climate is continental, meaning that we have sufficient sunny days, which also might contribute to the levels of vitamin D (13,14).…”
Section: Discussionmentioning
confidence: 99%